2018
DOI: 10.1161/hypertensionaha.117.10799
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial PPARγ (Peroxisome Proliferator–Activated Receptor-γ) Is Essential for Preventing Endothelial Dysfunction With Aging

Abstract: Little is known about mechanisms that control vascular aging, particularly at the cell-specific level. PPARγ (peroxisome proliferator-activated receptor-γ) exerts protective effects in the vasculature when activated pharmacologically. To gain insight into the cell-specific impact of PPARγ, we examined the hypothesis that genetic interference with endothelial PPARγ would augment age-induced vascular dysfunction. We studied carotid arteries from adult (11.6±0.3 months) and old (24.7±0.6 months) mice with endothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 44 publications
1
16
0
Order By: Relevance
“…Its disruption leads to disorders of fatty acid/lipid metabolism, insulin resistance, and vascular pathology. Endothelial PPARγ is essential for preventing endothelial dysfunction with aging (42,43). Impaired endothelial PPARγ causes age-related vascular dysfunction.…”
Section: Disruption Of Pparγ In Endothelial Dysfunction Of Drmentioning
confidence: 99%
“…Its disruption leads to disorders of fatty acid/lipid metabolism, insulin resistance, and vascular pathology. Endothelial PPARγ is essential for preventing endothelial dysfunction with aging (42,43). Impaired endothelial PPARγ causes age-related vascular dysfunction.…”
Section: Disruption Of Pparγ In Endothelial Dysfunction Of Drmentioning
confidence: 99%
“…A subpressor dose of Ang-II (120 ng/kg/min) was employed because we previously showed that E-V290M exhibit increased susceptibility and sensitivity to stressors including high fat diet, Ang-II and aging. 23,25,27 Administration of a sub-pressor dose of Ang-II did not affect SBP irrespective of genotype or pregnancy in either male or female offspring (Figure 2A). Endothelium-dependent relaxation was not affected in Ang-II-treated male nor female NT offspring born from AVP-infused pregnancies (Figure 2B).…”
Section: Resultsmentioning
confidence: 93%
“…Adult male and female transgenic mice expressing a dominant-negative mutation in human PPARγ under the control of an endothelial-specific vascular cadherin promoter (E-V290M) were used as experimental models as described below. 23,[25][26][27] Animals were maintained in conventional housing on a standard 12-hour light cycle with ambient temperature of 25°C. Mice were fed standard chow and were allowed drinking water ad libitum.…”
Section: Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…As introduced above, a large number of risk factors plays a role in the development of CVDs, especially ageing which is associated with well-characterized phenotypes [8,13,14]. Over time, aged blood vessels become stiffer and thicker, and their ability to release vasoactive mediators, particularly NO, decreases, while vascular permeability increases, associated with the process of mild vessel inflammation, increased vessel thickness and compromised angiogenic response [14][15][16][17][18]. Of note, even if age remains the main determinant of vascular senescence, healthy vascular ageing can be achieved, and endothelial function is a key element of the heathy vasculature.…”
Section: Endothelial Senescencementioning
confidence: 99%